A Remark on Unit Root Tests and Measures of Persistence - Marco Bianchi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
In this paper we simulate a series which is segmented trend plus noise. Despite the imposed data generating process, usual tests for unit roots and estimates of persistence fail to reject the random walk hypothesis.
Keywords: 330